Exploring Lecturers Ethical Dilemmas in Digital Communication: A Case Study of Telegram Usage in College Education in Russia - Ekaterina A. Santanna (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
This research examined the ethical implications of using Telegram chats in college education, focusing on the Social Penetration Theory (SPT) to understand its impact on interpersonal relationships. The study aims to identify ethical dilemmas faced by lecturers and chat administrators. Data was collected from the Creative Industry Faculty in Novosibirsk, Russia, using hermeneutic phenomenological interviewing between February and April 2023. The sample includes six female lecturers (age M=35, SD=15) and three chat administrators (two female, one male; age M=20, SD=2), who provided written consent and used pseudonyms. The findings of this research revealed ethical concerns such as students seeking attention and engaging in provocative behavior through jokes and intolerant remarks. Students also desired more informal communication with lecturers, crossing boundaries by sharing personal problems and engaging in discussions involving partying, smoking, and alcohol use. These behaviors presented ethical dilemmas for lecturers and chat administrators, including decisions about sharing received information and addressing online behavior offline. The study highlights the need for ethical regulations in online college communication. Limitations include the small sample size, and future research should include more diverse groups of lecturers and officials from various college departments.